2019
DOI: 10.3390/molecules24142585
|View full text |Cite
|
Sign up to set email alerts
|

Plants are Capable of Synthesizing Animal Steroid Hormones

Abstract: As a result of the findings of scientists working on the biosynthesis and metabolism of steroids in the plant and animal kingdoms over the past five decades, it has become apparent that those compounds that naturally occur in animals can also be found as natural constituents of plants and vice versa, i.e., they have essentially the same fate in the majority of living organisms. This review summarizes the current state of knowledge on the occurrence of animal steroid hormones in the plant kingdom, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 76 publications
1
29
0
1
Order By: Relevance
“…From (Fig. 2), it is observed that ethanolic extraction method failed to extract steroids from A. Vasica leaves while chloroform as solvent proved to extract these phytosterols may also act as precursors for the de novo biosynthesis of steroid hormones [16].. Flavonoids, terpenoids and saponins (Fig. 3, 4 & 5) were present in both extracts which shows promising capabilities of both extracts for prevention and treatment of many degenerative diseases.…”
Section: Phytochemical Analysismentioning
confidence: 94%
“…From (Fig. 2), it is observed that ethanolic extraction method failed to extract steroids from A. Vasica leaves while chloroform as solvent proved to extract these phytosterols may also act as precursors for the de novo biosynthesis of steroid hormones [16].. Flavonoids, terpenoids and saponins (Fig. 3, 4 & 5) were present in both extracts which shows promising capabilities of both extracts for prevention and treatment of many degenerative diseases.…”
Section: Phytochemical Analysismentioning
confidence: 94%
“…Brassinosteroids (BRs) are considered as a novel candidate of steroids that play a crucial role in antiviral activities in the recovery of patients suffering with herpetic and viral diseases [91]. Four analogues of 28-homocastasterone such as (22R,23R,24S)-3β-acetoxy-22, 23-dihydroxy-5α-stigmastan-6-one (1), (22R,23R,24S)-3β-bromo-22,23-dihydroxy-5α-stigmastan-6-one (2), (22R,23R,24S)-3β-acetoxy-5, 22, 23-trihydroxy-5α-stigmastan-6-one (3), and (22R,23R,24S) 3β-bromo-5,22,23-trihydroxy-5α-stigmastan-6-one [4] have been formed via an artificial pathway dependent upon regioselective ∆ 5 epoxidation and characterization was done from stigmasterol. Compounds 1 and 2 having a 5αH moiety were synthesized by a reductive opening of the 5β, 6β epoxy precursor, and compounds 3 and 4 having 5αOH moiety were attained through hydrolytic opening of a mixture of 5α, 6α and 5β, 6β epoxy precursors.…”
Section: Antiherpetic Activitiesmentioning
confidence: 99%
“…Even though steroids are primarily associated with mammals due to early investigations and drug productions, it has been demonstrated that steroids are also natural components of all other eukaryotes including plants, where they also are involved in regulation of the physiological processes related to growth, development, and reproduction [ 12 , 13 ].…”
Section: Biosynthesis Of Steroid Hormones In Mammalsmentioning
confidence: 99%
“…Phytosterols can be precursors for heterologous biosynthesis of steroid hormones [ 13 ] such as phytoecdysteroids, brassinosteroids [ 36 ], progesterone, testosterone, and its derivatives [ 13 ]. Androsteroid functions are not limited to reproduction; they are also involved in controlling plant vegetative development.…”
Section: Biosynthesis Of Androsteroids In Plantsmentioning
confidence: 99%
See 1 more Smart Citation